(untitled) (UNIZIK Journal of STM Education, 2025)
This study investigated prosocial behaviour and academic interest as predictors of academic achievement in Chemistry among secondary school students in Awka South Local Government Area. The study is guided by three research questions and three postulated research hypotheses. Participants were drawn from 10 randomly selected secondary schools in Awka South LGA. 260 Participants were selected through a simple random sampling technique consisting of 130 boys and 130 girls. The study adopted a cross-sectional survey design. Two research instruments were used in the present study, they are Prosocialness Scale (PS) and Academic Interest Scale for Adolescents (AISA). Analysis of data was conducted using the multiple regression statistic. Results indicate that prosocial behaviour and academic interest account for 24.4%% of variance in academic achievement (R = .494, R² = .244, F (2, 257) = 41.47, p < .001) indicating a strong joint prediction. Independently, prosocial behaviour significantly and positively predicts academic achievement in chemistry (β = .239, P < .05). Similarly, academic interest significantly and positively predicted academic achievement in Chemistry (β = .417, P < .05). Relative to research findings, it is recommended that teachers should receive professional development since they have a significant influence on students’ prosocial behavior and academic interest. Schools should thus fund professional development initiatives that give educators the tools they need to inspire students, foster inclusive learning environments, and encourage group projects. Training sessions could concentrate on employing student-centered teaching methods, controlling group dynamics, and encouraging intrinsic drive.